Genome-wide screen of gamma-secretase-mediated intramembrane cleavage of receptor tyrosine kinases - Merilahti JAM; Ojala VK; Knittle AM; Pulliainen AT; Elenius K (AMER SOC CELL BIOLOGY, 2022)
Receptor tyrosine kinases (RTKs) have been demonstrated to signal via regulated intramembrane proteolysis, in which ectodomain shedding and subsequent intramembrane cleavage by gamma-secretase leads to release of a soluble intracellular receptor fragment with functional activity. For most RTKs, however, it is unknown whether they can exploit this new signaling mechanism. Here we used a system-wide screen to address the frequency of susceptibility to gamma-secretase cleavage among human RTKs. The screen covering 45 of the 55 human RTKs identified 12 new as well as all nine previously published gamma-secretase substrates. We biochemically validated the screen by demonstrating that the release of a soluble intracellular fragment from endogenous AXL was dependent on the sheddase disintegrin and metalloprotease 10 (ADAM10) and the gamma-secretase component presenilin-1. Functional analysis of the cleavable RTKs indicated that proliferation promoted by overexpression of the TAM family members AXL or TYRO3 depends on gamma-secretase cleavage. Taken together, these data indicate that gamma-secretase-mediated cleavage provides an additional signaling mechanism for numerous human RTKs.